2005
DOI: 10.1093/humrep/dei412
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonial survival after grafting human testicular tissue to immunodeficient mice

Abstract: After xenografting human adult testicular tissue to a recipient mouse, spermatogonia were maintained over a period of >195 days. However, in order to prove xenografting as a method for external germ line storage, the transplants should have a more immature developmental stage. Moreover, not only the developmental status of the tissue at the time-point of grafting, but also the structural organisation of the seminiferous epithelium, might influence the development of the testicular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 34 publications
7
81
0
1
Order By: Relevance
“…Xenografting of testis tissues from pig or goat under the skin of immunodeficient mice has been reported to result in complete spermatogenesis (17). Xenografting of human testis tissues has been attempted, but only spermatogonia were obtained (18,19). Xenogeneic spermatogenesis also raises ethical issues and presents the risk of transmission of animal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Xenografting of testis tissues from pig or goat under the skin of immunodeficient mice has been reported to result in complete spermatogenesis (17). Xenografting of human testis tissues has been attempted, but only spermatogonia were obtained (18,19). Xenogeneic spermatogenesis also raises ethical issues and presents the risk of transmission of animal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that xenografted testis tissue from sexually mature donors is less successful than that from sexually immature donors (Arregui et al 2008). Moreover, complete spermatogenesis has been reported to be absent in the xenografts that contained post-meiotic germ cells at the time of grafting in all species analyzed to date, and most of the mature donor grafts regressed or were found to contain degenerated tubules , Geens et al 2006, Arregui et al 2008, Abrishami et al 2010. Spermatogenesis was arrested at meiosis in grafts from mature horse (Rathi et al 2006), dog (Abrishami et al 2010) and photoregressed hamster testes .…”
Section: Introductionmentioning
confidence: 99%
“…Xenografting of immature testis tissue from several species, including the rhesus macaque, into a nude mouse host results in full spermatogenesis within the grafted tissue (Honaramooz et al, 2004;Rodriguez-Sosa and Dobrinski, 2009). Previous reports of human testis xenografts show limited survival when post-natal tissue is grafted (Geens et al, 2006;Schlatt et al, 2006) and studies of fetal testis xenografts have been limited to descriptive reports of small numbers of second-trimester grafts Skakkebaek et al, 1974;Yu et al, 2006). Therefore, the aim of the present study was to investigate the suitability of human fetal testis xenografting as a technique to recapitulate normal fetal testis development, including germ cell differentiation.…”
Section: Introductionmentioning
confidence: 99%